Risk management practices and firm performance with a mediating role of Business Model Innovation: Observations from Jordan - Munther Al-Nimer; Sinan S. Abbadi; Ahmad Al-Omush; Habib Ahmad (Journal of Risk and Financial Management, 2021)
This study focused on scrutinizing the influence of Enterprises Risk Management (ERM) on firm performance with a mediating role of Business Model Innovation (BMI). For the purpose, data from 228 Jordanian firms was collected and analyzed. The results indicated that the ERM practices have a significant influence on BMI and financial firm's performance. The BMI significantly contributed to the financial and nonfinancial performance, whereas it displayed insignificant effects regarding environmental performance. The BMI fully mediated the relationship between ERM practices and financial performance, where a partial mediating effect was observed for the path between ERM practices and nonfinancial performance, while showed no mediating role between the ERM practices and environmental performance. Economies of countries like Jordan are hereby urged to implement the formal ERM practices and to financially educate their top management teams to apply the BMI to gain first-rate performance. This study also encourages the researchers from other countries to extend this model to their economies to unleash useful insights.
Keywords: 330; financial performance; Business Model Innovation; emerging markets; enterprise risk management practices; financial sector